2023
DOI: 10.1002/fsn3.3230
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bifidobacteriumlactis IDCC 4301 isolated from breast milk‐fed infant feces as a probiotic and functional ingredient

Abstract: Probiotics provide important health benefits to the host by improving intestinal microbial balance and have been widely consumed as dietary supplements. In this study, we investigated whether Bifidobacterium lactis IDCC 4301 (BL), isolated from feces of breast milk‐fed infants, is safe to consume. Based on the guidelines established by the European Food Safety Authority (EFSA), safety tests such as antibiotic susceptibility, hemolysis, toxic compound formation (i.e., biogenic amine and d‐lactate), single‐dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Particularly, it could be severe problems in infants an in patients with short bowel syndrome. Thus, the FAO/WHO requires information about D-lactate production to assess the safety of probiotics, and recommended that the product label should specify the information about strains that produce D-lacate ( 76 , 77 ). In this study, we confirmed that L. paracasei AO356 mainly produced L-lactate and rarely produced D-lactate, which is similar to L. rhamnosus GG , commercial probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it could be severe problems in infants an in patients with short bowel syndrome. Thus, the FAO/WHO requires information about D-lactate production to assess the safety of probiotics, and recommended that the product label should specify the information about strains that produce D-lacate ( 76 , 77 ). In this study, we confirmed that L. paracasei AO356 mainly produced L-lactate and rarely produced D-lactate, which is similar to L. rhamnosus GG , commercial probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the antipathogenic effects of L. paracasei IDCC 3401, a previously described method [ 28 ] was used with a minor modification. The supernatants of L. paracasei IDCC 3401 were harvested via centrifugation at 8000 rpm and 4 °C for 30 min, followed by filtering through a 0.20 µm syringe filter to remove residual bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Their decline has been linked to an elevated risk of immune–metabolic conditions such as obesity, T2DM, and metabolic syndrome [ 89 , 90 , 91 ]. The two most frequent genera are Lactobacillus and Bifidobacterium [ 92 ]. Despite the absence of approval from medical regulatory authorities like the European Food Safety Authority and the US Food and Drug Administration for any probiotic formulation as a therapeutic agent [ 93 , 94 , 95 ], in compliance with the guidelines established by the Ministry of Food and Drug Safety (MFDS) for healthful functional foods, South Korea uses 19 probiotic species as functional ingredients.…”
Section: Probiotics Prebiotics Synbiotics and Postbiotics In The Mana...mentioning
confidence: 99%